Bicycle Rental Management System for UTHM Student - Mardiustari, Nurul Najwa; Rozita Abdul Jalil (Applied Information Technology And Computer Science, 2025)
A comprehensive digital platform called the "Bicycle Rental Management System for UTHM Students" was created to completely transform University Tun Hussein Onn Malaysia (UTHM) students’ mobility experience. The main objective of this system is to make short-term bicycle rentals easily accessible to UTHM students. The system includes intuitive mobile and online interfaces for bike booking, real-time tracking, administrative monitoring, and registration. This system comprises many important components, such as booking administration, payment processing, user authentication, and inventory control for bicycles. Students may register, access rental services, pay reserve bicycles for particular times, and manage their rentals using a web-based system. The system was developed using PHP and MySQL. The data of the students will be saved into the database automatically when they register their account to the website. In the dashboard, student can see the page of Bicycle List that allow them to chos their bicycle. After that, they will have to set their time to rent the bicycle. The process will last for the payment process that user need to pay the rental cost.